A nationwide study of obstetric management and outcomes in premature rupture of membrane at term: Report from the Perinatology Committee, Japan Society of Obstetrics and Gynecology, 2017–2018. Issue 1 (4th October 2022) - Oda, Tomoaki; Mitsuda, Nobuaki; Miyakoshi, Kei; Makino, Shintaro; Ishii, Keisuke; Kurasawa, Kentaro; Kubo, Takahiko; Shimoya, Koichiro; Ikeda, Tomoaki; Kanayama, Naohiro
Abstract: Aim: This nationwide study aimed to investigate the practical management of term premature rupture of membrane (PROM) and its relationship with maternal and neonatal outcomes. Methods: We conducted a questionnaire survey of 415 facilities participating in the Japan Perinatal Registry Network of the Japan Society of Obstetrics and Gynecology in 2016. The patients were women expecting vaginal birth after PROM at term without clinical chorioamnionitis. We classified the facilities into three groups based on duration of the expectant management after PROM (within 24, 24, and 48 h). Furthermore, we analyzed the association between perinatal outcomes and management protocol using the Japan Perinatal Registry Network Database 2016. Results: Of 415 facilities, 346 (83.4%) completed and returned the survey. Among 231 facilities with management protocols, an interval of 3 days from PROM to delivery was acceptable in 167 facilities (72.3%). One hundred forty‐nine facilities (64.5%) responded that they did not perform mechanical cervical dilation, and 90 (39.0%) used oxytocin as a uterotonic irrespective of cervical maturation. The number of hospitals that had a policy to administer antibiotics to Group B streptococcus‐positive patients was 211 (91.3%). Neonatal outcomes at birth and the frequency of cesarean section and postpartum fever did not differ among the three groups. Conclusions: Most facilities in the Japan Perinatal Registry Network managed women at term to delivery within 3 days after PROM with attention to bacterial infection. Expectant management up to 48 h after PROM did not increase the risk of postpartum fever, compared to labor induction immediately after PROM.